Resin composition, manufacturing method thereof and substrate structure
By crosslinking the resin composition that does not require a triallyl isocyanurate crosslinking agent, including hydrocarbon resin polymer and divinyl aromatic compounds, the problems of smoke generation and organic solvent use in the copper foil substrate manufacturing process are solved, and the low-cost, low-energy-consuming and environmentally friendly substrate structure manufacturing is achieved, and thermal performance and electrical performance are improved.
Patent Information
- Application Number
- CN202411136470.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-07-29
- Filing Date
- 2024-08-19
- Publication Date
- 2025-02-25
AI Technical Summary
The triallyl isocyanurate crosslinking agent used in the manufacturing process of existing copper foil substrates is prone to thermal decomposition or volatilization at high temperatures, resulting in smoke generation. In addition, the preparation of hydrocarbon resin polymers requires the use of organic solvents, which affects environmental protection and cost.
The crosslinking is performed by including hydrocarbon resin polymers and divinyl aromatic compounds using resin compositions that do not require a triallyl isocyanurate crosslinking agent, reducing the crosslinking temperature and time, and reducing or avoiding the use of organic solvents.
A low-cost, low-energy-consuming and environmentally friendly substrate structure manufacturing is achieved, and the resin composition has good thermal properties and electrical properties, and does not emit smoke during the cross-linking process.
Smart Images

Figure CN119505099A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a resin composition, a method for producing the resin composition and a substrate structure comprising the resin composition, and more particularly to a resin composition comprising a hydrocarbon resin polymer, a method for producing the resin composition and a substrate structure comprising the resin composition. Background Art
[0002] Due to the rise of cloud, interconnection, and the Internet of Things, and the improvement of 5G communication technology and display technology, the material requirements for circuit boards and integrated circuit carriers (IC carriers) required by the optoelectronics, communication, and semiconductor industries are becoming more and more stringent. Copper clad laminate (CCL) is an important material commonly used in electronic products, which is mainly used to manufacture circuit boards. Hydrocarbon resin polymers or polyolefin materials composed of carbon and hydrogen atoms have low dielectric loss characteristics due to their small number of polar functional groups. Therefore, polymerizable hydrocarbon resin polymers can be used as materials for copper clad laminates or integrated circuit carriers.
[0003] Triallyl isocyanurate (TAIC) is often used as a cross-linking agent to cross-link with various resins (such as hydrocarbon resin polymers) to form a resin layer in a copper foil substrate. However, the use of triallyl isocyanurate as a cross-linking agent may cause fuming. Specifically, the manufacturing process of the copper foil substrate involves a high-temperature treatment stage, which may cause thermal decomposition or volatilization (i.e., fuming) of triallyl isocyanurate. In addition, organic solvents are usually used for purification during the preparation of polymerizable hydrocarbon resin polymers. The use of organic solvents is not environmentally friendly and will lead to increased costs. Summary of the invention
[0004] In view of the above problems, the present invention provides a resin composition, which does not require the use of a triallyl isocyanurate crosslinking agent during crosslinking and / or can be crosslinked at a lower crosslinking temperature or a shorter crosslinking time. The resin composition of the present invention does not require or can reduce the use of organic solvents during preparation. The substrate structure prepared using the resin composition of the present invention can be obtained in a low-cost, low-energy, and / or environmentally friendly manner. In addition, the substrate structure prepared using the resin composition of the present invention can have good thermal properties (high glass transition temperature (glass transition temperature, Tg)) or good electrical performance.
[0005] In some embodiments, the present invention provides a resin composition comprising 100 parts by weight of a hydrocarbon resin polymer and 0.01 to 50 parts by weight of a divinyl aromatic compound.
[0006] In some embodiments, the present invention provides a method for preparing a resin composition, comprising: providing a mixture; polymerizing the mixture to form a crude composition; and purifying the crude composition, wherein the mixture comprises an optional bridged ring compound, a monovinyl aromatic compound, and a divinyl aromatic compound. The prepared resin composition comprises 100 parts by weight of a hydrocarbon resin polymer and 0.01 to 50 parts by weight of a divinyl aromatic compound.
[0007] In some embodiments, the present invention provides a substrate structure, which includes a base layer, a conductive layer disposed on the base layer, and a resin layer disposed between the conductive layer and the base layer. The resin layer is formed by a resin composition through a cross-linking process, and the resin composition includes 100 parts by weight of a hydrocarbon resin polymer and 0.01 to 50 parts by weight of a divinyl aromatic compound. BRIEF DESCRIPTION OF THE DRAWINGS
[0008] In order to make the purpose, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below with reference to the accompanying drawings, wherein:
[0009] Figure 1 is a flow chart of a method for manufacturing a resin composition according to one embodiment of the present invention;
[0010] Figure 2 is a schematic diagram of a substrate structure according to an embodiment of the present invention;
[0011] Figure 3 is a graph showing the relationship between the storage modulus and the loss modulus and the temperature of the resin composition according to one embodiment of the present invention;
[0012] Figure 4 is a graph showing the relationship between the storage modulus and the loss modulus of a resin composition according to an embodiment of the present invention and time;
[0013] Figure 5 is a graph showing the relationship between the composite viscosity and time of a resin composition according to an embodiment of the present invention;
[0014] Figure 6 is a graph showing the relationship between the glass transition temperature of a substrate sample of the resin composition according to the present invention and the DVB content in the resin composition;
[0015] Figure 7 is a graph showing the relationship between the flow of the substrate sample of the resin composition according to the present invention and the DVB content in the resin composition; and
[0016] Figure 8 4 is a graph showing the relationship between the loss factor (Df) of the substrate sample of the resin composition according to the present invention and the DVB / TAIC content in the resin composition.
[0017]
Explanation of symbols
[0018] S101, S103, S105, S107: Step 200: Base layer
[0019] 200S1: First surface
[0020] 200S2: Second surface
[0021] 201,202: resin layer
[0022] 203,204: Conductive layer DETAILED DESCRIPTION
[0023] It will be further understood that when "include" and / or "comprising" are used in this specification, they specifically refer to the presence of the characteristic parts, integers, steps, operations, components, ingredients, and / or their groups, but do not exclude the presence or addition of one or more other characteristic parts, integers, steps, operations, components, ingredients, and / or their groups. When the singular form "a" is used in this specification, it is also intended to include the plural form unless the context clearly indicates otherwise.
[0024] It will be understood that although the terms "first", "second", etc. may be used herein to describe various components, components, regions, layers and / or parts, these components, components, regions, layers and / or parts should not be limited by these terms. These terms are only used to distinguish one component, component, region, layer or part from another component, component, region, layer or part.
[0025] It will be understood that the terms "about", "approximately", and "roughly" herein generally refer to within 20% of a given value or range, preferably within 10%, and more preferably within 5%, or within 3%, or within 2%, or within 1%, or within 0.5%. The quantity given here is an approximate quantity, that is, in the absence of a specific description of "about", "approximately", or "roughly", the meaning of "about", "approximately", or "roughly" may still be implied. Further, the numerical values represented in the present invention may include the numerical values and deviation values within the deviation range acceptable to those of ordinary knowledge in the art. It will be understood that the expression "a~b" used herein to represent a specific numerical range is defined as "≧a and ≦b".
[0026] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meanings as those commonly understood by those skilled in the art. It is understood that these terms, such as those defined in commonly used dictionaries, should be interpreted as having a meaning consistent with the background or context of the relevant technology and the present application, and should not be interpreted in an idealized or overly formal manner unless specifically defined in the present invention. The following will omit descriptions that may unnecessarily confuse the known functions and structures of the present invention.
[0027] In the present invention, "C 1-20 "Alkyl" refers to a linear, branched or cyclic aliphatic hydrocarbon monovalent group having 1 to 20 carbon atoms in the main carbon chain. 1-20 Examples of the alkyl group may include methyl, ethyl, propyl, isobutyl, sec-butyl, tert-butyl, pentyl, isopentyl, hexyl, dodecyl, dodecyl, cyclohexyl, cyclooctyl, and cyclododecyl, but the present invention is not limited thereto.
[0028] In the present invention, "C 2-20 "Alkenyl" refers to a linear, branched or cyclic aliphatic hydrocarbon monovalent group having 2 to 20 carbon atoms and at least one carbon-carbon double bond in the main carbon chain. 2-20 Non-limiting examples of alkenyl groups include, but are not limited to, ethenyl, propenyl, isobutenyl, sec-butenyl, tert-butenyl, pentenyl, isopentenyl, hexenyl, decenyl, dodecenyl, pentadecenyl, cyclohexenyl, cyclooctenyl, cyclopentenyl, cyclopentadienyl, and cyclopentadecenyl.
[0029] The "bridged ring compound" in the present invention refers to a compound including a bridged ring structure. A bridged ring structure refers to a compound including at least two carbon rings, and the at least two carbon rings share two carbon atoms that are not directly connected. Examples of bridged ring compounds may include norbornene (NB), dicyclopentadiene (DCPD), norbornadiene (NBD), 2-acetyl-5-norbornene, methyl5-norbornene-2-carboxylate, vinyl norbornene, and ethylidene-norbornene, but the present invention is not limited thereto.
[0030]
[0031]
[0032] Some embodiments of the present invention provide a resin composition comprising 100 parts by weight of a hydrocarbon resin polymer and 0.01 to 50 parts by weight of a divinyl aromatic compound. The hydrocarbon resin polymer in the resin composition of the present invention includes a crosslinkable group. In some embodiments, the crosslinkable group may include an unsaturated group, an epoxy group or a hydroxyl group or a combination thereof, but the present invention is not limited thereto. By making the resin composition of the present invention include more than 0.01 parts by weight of a divinyl aromatic compound, in some embodiments, the resin composition of the present invention can be crosslinked without further adding a crosslinking agent. By making the resin composition of the present invention include less than 50 parts by weight of a divinyl aromatic compound, the resin composition of the present invention can have an appropriate viscosity, thereby having better processability. In some embodiments, based on 100 parts by weight of a hydrocarbon resin polymer, the resin composition of the present invention may include 0.1 to 48 parts by weight, 0.2 to 45 parts by weight, or 0.4 to 43 parts by weight of a divinyl aromatic compound.
[0033] The storage modulus of the resin composition of the present invention exceeds the loss modulus at about 125°C to 165°C. That is, the solid state properties of the resin composition of the present invention exceed the liquid state properties in the temperature range of about 125°C to 165°C, indicating that the crosslinkable temperature of the resin composition is within this temperature range. A detailed method for measuring the crosslinkable temperature will be described later. The resin composition of the present invention has a crosslinkable temperature of about 125°C to 165°C. In some embodiments, the resin composition may have a crosslinkable temperature of about 135°C to 163°C or 135°C to 160°C. In some embodiments, the resin composition may have a crosslinkable temperature of about 140°C to 155°C. The lower the crosslinkable temperature, the lower the crosslinking temperature at which the resin composition can perform the crosslinking process, thereby reducing the energy required during the crosslinking process.
[0034] The resin composition of the present invention may have a storage modulus of about 10,000 to 10,000,000 Pa after a crosslinking time of 2,000 seconds at a crosslinking temperature of 160° C. In some embodiments, the resin composition has a storage modulus of about 20,000 to 9,000,000 Pa or 21,000 to 8,500,000 Pa after a crosslinking time of 2,000 seconds at a crosslinking temperature of 160° C. In some embodiments, the resin composition has a storage modulus of about 100,000 to 2,000,000 Pa or 200,000 to 1,000,000 Pa after a crosslinking time of 2,000 seconds at a crosslinking temperature of 160° C.
[0035] The crosslinking time corresponding to the storage modulus obtained by multiplying the storage modulus of the resin composition obtained by a crosslinking temperature of 160°C and a crosslinking time of 2,000 seconds by 0.9 is defined as the "required crosslinking time". In some embodiments, the "required crosslinking time" of the resin composition of the present invention is about 1300 to 1900 seconds, which means that the resin composition of the present invention can substantially complete the crosslinking process after a crosslinking time of about 1300 to 1900 seconds. In some embodiments, the "required crosslinking time" of the resin composition of the present invention is about 1700 to 1850 seconds.
[0036] The resin composition of the present invention can have a crosslinking temperature of about 160°C after half of the above-mentioned "required crosslinking time". 4 ~6.00×10 8 Complex viscosity of cP; for example, 1.00×10 6 ~1.00×10 8 cP, 1.00×10 7 ~1.00×10 8 cP, 1.00×10 7 ~5.00×10 7 cP.
[0037] In some embodiments, the hydrocarbon resin polymer in the resin composition of the present invention may include repeating units (B) derived from a monovinyl aromatic compound and repeating units (C) derived from a divinyl aromatic compound.
[0038] Here, the monovinyl aromatic compound refers to a compound including a carbocyclic aromatic structure, and one hydrogen atom on the ring-forming carbon atom of the carbocyclic aromatic structure is replaced by a vinyl group. In some embodiments, the vinyl group may be unsubstituted. In some embodiments, at least one hydrogen atom on the vinyl group may be replaced by a C 1-20 In some embodiments, the carbocyclic aromatic structure may include 6 to 60 or 6 to 20 ring-forming carbon atoms. In some embodiments, the carbocyclic aromatic structure may be unsubstituted. In some embodiments, at least one hydrogen on the ring-forming carbon atom in the carbocyclic aromatic structure may be replaced by a C 1-20 Examples of the monovinyl aromatic compound may include styrene, methylstyrene, or ethylstyrene, but the present invention is not limited thereto.
[0039] The repeating unit (B) derived from a monovinyl aromatic compound includes a carbocyclic aromatic structure derived from a monovinyl aromatic compound. For example, in some embodiments, the repeating unit (B) may have the following structure, but the present invention is not limited thereto:
[0040] The "*" in the above structure indicates the contact position with other groups or units.
[0041] Here, the divinyl aromatic compound refers to a compound including a carbocyclic aromatic structure, and two hydrogen atoms on the ring carbon atoms of the carbocyclic aromatic structure are replaced by vinyl groups. In some embodiments, the vinyl group may be unsubstituted. In some embodiments, at least one hydrogen atom on the vinyl group may be replaced by a C 1-20 In some embodiments, the carbocyclic aromatic structure may include 6 to 60 or 6 to 20 ring-forming carbon atoms. In some embodiments, the carbocyclic aromatic structure may be unsubstituted. In some embodiments, at least one hydrogen on the ring-forming carbon atom of the carbocyclic aromatic structure may be replaced by a C 1-20 Examples of the divinyl aromatic compound may include divinylbenzene or diisopropenylbenzene, but the present invention is not limited thereto.
[0042] The repeating unit (C) derived from the divinyl aromatic compound includes a carbocyclic aromatic structure derived from the divinyl aromatic compound. In some embodiments, the repeating unit (C) may include a cross-linkable repeating unit (C1) and a cross-linked repeating unit (C2):
[0043]
[0044] R1, R2, R3, and R4 in the crosslinkable repeating unit (C1) and the crosslinked repeating unit (C2) may each independently be H or C 1-20 alkyl, and Ar1 and Ar2 may be phenyl groups; * represents the connection position between the cross-linkable repeating unit (C1) and / or the cross-linked repeating unit (C2) and other groups or units. In some embodiments, the cross-linkable repeating unit (C1) may include the following structure, but the present invention is not limited thereto: In some embodiments, the cross-linked repeating unit (C2) may include a structure as shown below, but the present invention is not limited thereto:
[0045]
[0046] In some embodiments, based on 100 mol% of the hydrocarbon resin polymer, the hydrocarbon resin polymer may include 15 to 95 mol% of repeating units (B) and 5 to 85 mol% of repeating units (C). When the content of repeating units (B) and repeating units (C) in the hydrocarbon resin polymer is within the above range, the hydrocarbon resin polymer may have better thermal properties and / or processability. In some embodiments, based on 100 mol% of the hydrocarbon resin polymer, the hydrocarbon resin polymer may include 35 to 94 mol% of repeating units (B) and 6 to 55 mol% of repeating units (C), 45 to 93 mol% of repeating units (B) and 7 to 45 mol% of repeating units (C), or 55 to 92 mol% of repeating units (B) and 8 to 35 mol% of repeating units (C). In some embodiments, based on 100 mol% of the hydrocarbon resin polymer, the hydrocarbon resin polymer may include 1 to 30 mol% of cross-linkable repeating units (C1). When the content of the cross-linkable repeating unit (C1) in the hydrocarbon resin polymer is within the above range, the hydrocarbon resin polymer may have better thermal properties, electrical properties, and / or processability.
[0047] In some embodiments, the hydrocarbon resin polymer in the resin composition of the present invention may further include a repeating unit (A) derived from a bridged ring compound. In some embodiments, the bridged ring compound may include 3 to 12 ring-forming atoms and 1 to 2 double bonds. In some embodiments, the bridged ring compound may be unsubstituted. In some embodiments, at least one hydrogen atom on the bridged ring compound may be selected from C 1-20 Alkyl, C 2-20 In some embodiments, the bridged ring compound has at least two substituents, which can be selected from C 1-20 Alkyl, C 2-20 Any two substituents from the group consisting of an alkenyl group, or a carboxylate group having 1 to 20 carbon atoms on the main carbon chain. Adjacent substituents in the at least two substituents may form a ring together. In some embodiments, examples of the bridged ring compound may include dicyclopentadiene or norbornene, but the present invention is not limited thereto.
[0048] In some embodiments, the repeating unit (A) may have the following structure, but the present invention is not limited thereto:
[0049]
[0050] The "*" in the above structure indicates the connection position with other groups or units. Compared with linear repeating units, the repeating unit (A) derived from the bridged ring compound has higher rigidity, so it can increase the glass transition temperature of the hydrocarbon resin polymer or improve the thermal properties of the hydrocarbon resin polymer.
[0051] In some embodiments, based on 100 mol% of the hydrocarbon resin polymer, the hydrocarbon resin polymer may include 0.15 to 15 mol% of the repeating unit (A). When the content of the repeating unit (A) in the hydrocarbon resin polymer is within the above range, the hydrocarbon resin polymer may have better thermal properties and lower manufacturing costs. In some embodiments, based on 100 mol% of the hydrocarbon resin polymer, the hydrocarbon resin polymer may include 0.5 to 12 mol%, 1 to 10 mol%, or 1.5 to 8 mol% of the repeating unit (A).
[0052] In some embodiments, based on 100 mol% of the hydrocarbon resin polymer, the sum of the contents of the repeating unit (A) and the repeating unit (C) of the hydrocarbon resin polymer is greater than or equal to 13 mol%. The repeating unit (A) and the repeating unit (C) will affect the thermal properties and thermal stability of the hydrocarbon resin polymer. The sum of the repeating unit (A) and the repeating unit (C) greater than or equal to 13 mol% can provide the hydrocarbon resin polymer with excellent thermal properties and thermal stability. In some embodiments, based on 100 mol% of the hydrocarbon resin polymer, the sum of the contents of the repeating unit (A) and the repeating unit (C) of the hydrocarbon resin polymer may be greater than or equal to 15 mol%, 17 mol%, or 20 mol%. In some embodiments, based on 100 mol% of the hydrocarbon resin polymer, the sum of the contents of the repeating unit (A) and the repeating unit (C) of the hydrocarbon resin polymer may be less than or equal to 45 mol%, 40 mol%, or 35 mol%.
[0053] In some embodiments, the hydrocarbon resin polymer may include reactive double bonds.
[0054] "Reactive double bonds" refer to double bonds in repeating unit (A) or repeating unit (C) that can react with other compounds or polymers. For example, in some embodiments, the reactive double bonds include the double bonds in repeating unit (A) shown below: Alternatively, the double bonds on the non-benzene ring in the repeating unit (C) are shown below: However, the present invention is not limited thereto.
[0055] In some embodiments, the hydrogen content on the reactive double bonds of the hydrocarbon resin polymer may be less than 10%. When the hydrogen content on the reactive double bonds in the hydrocarbon resin polymer is too high, for example, higher than 10%, the hydrocarbon resin polymer is easily oxidized during the heating process, resulting in poor electrical performance of the hydrocarbon resin polymer. In some embodiments, the hydrogen content on the reactive double bonds in the hydrocarbon resin polymer may be greater than 0.2%. When the hydrogen content on the reactive double bonds in the hydrocarbon resin polymer is too low, for example, lower than 0.2%, the peel strength of the layer including the hydrocarbon resin polymer may be too low. In some embodiments, the hydrogen content on the reactive double bonds in the hydrocarbon resin polymer may be 0.2% to 10%, 0.3% to 9%, 0.4% to 8%, or 0.5% to 7%. When the hydrogen content on the reactive double bonds in the hydrocarbon resin polymer is within the above range, the hydrocarbon resin polymer is not easily oxidized or tends to complete the cross-linking reaction before oxidation in a high temperature environment (for example, above 150°C), so the electrical performance of the hydrocarbon resin polymer can be improved. In some embodiments, the number average molecular weight (Mn) of the hydrocarbon resin polymer may be 2,500 to 15,000 g / mol. When the number average molecular weight of the hydrocarbon resin polymer is too high, the solubility of the hydrocarbon resin polymer may be reduced. In some embodiments, the number average molecular weight (Mn) of the hydrocarbon resin polymer may be 2,500 to 13,000 g / mol, 2,800 to 12,000 g / mol, or 3,000 to 11,000 g / mol.
[0056] In some embodiments, the polymer dispersity index (PDI) of the hydrocarbon resin polymer may be less than 20. When the polymer dispersity index of the hydrocarbon resin polymer is less than 20, the hydrocarbon resin polymer has better processability. In some embodiments, the polymer dispersity index of the hydrocarbon resin polymer may be greater than 1.5. In some embodiments, the polymer dispersity index of the hydrocarbon resin polymer may be 1.5-20, 2-18, or 2.2-16.5.
[0057] In some embodiments, the resin composition may further include 5 to 350 parts by weight of a solvent. The resin composition having the above-mentioned content of the solvent may have good processability. In some embodiments, based on 100 parts by weight of the hydrocarbon resin polymer, the resin composition of the present invention may include 6 to 340 parts by weight, 10 to 340 parts by weight, or 30 to 340 parts by weight of a solvent. The solvent may be any possible organic solvent. In some embodiments, the solvent may be toluene.
[0058] In some embodiments, the resin composition may further include a monovinyl aromatic compound. In some embodiments, based on 100 parts by weight of the hydrocarbon resin polymer, the resin composition of the present invention may include 0.1 to 50 parts by weight, 0.1 to 40 parts by weight, or 0.1 to 30 parts by weight of the monovinyl aromatic compound. In some embodiments, the monovinyl aromatic compound may include styrene and / or ethylstyrene, but the present invention is not limited thereto.
[0059] The resin composition of the present invention having the above-mentioned components and component contents can have at least one of the advantages of low composition viscosity, low gel flow, low crosslinking temperature, short crosslinking time, high glass transition temperature, good electrical performance, and no smoke during the crosslinking process.
[0060] Some embodiments of the present invention provide a method for producing a resin composition. Figure 1 FIG. 1 is a flow chart of a method for producing a resin composition according to an embodiment of the present invention. Figure 1 As shown, the method for preparing the resin composition of the present invention comprises: step S101 of providing a mixture; step S103 of polymerizing the mixture to form a crude composition; step S105 of purifying the crude composition; and step S107 of adding a divinyl aromatic compound.
[0061] The mixture provided by step S101 includes optional bridged ring compounds, monovinyl aromatic compounds, and divinyl aromatic compounds. In some embodiments, the mixture provided by step S101 includes 0 to 50 mol% of bridged ring compounds, 60 to 95 mol% of monovinyl aromatic compounds, and 0.5 to 15 mol% of divinyl aromatic compounds based on 100 mol% of the mixture. In some embodiments, the mixture provided by step S101 includes 0 to 30 mol% of bridged ring compounds, 65 to 95 mol% of monovinyl aromatic compounds, and 0.5 to 12 mol% of divinyl aromatic compounds based on 100 mol% of the mixture. In some embodiments, the mixture provided by step S101 includes 0 to 25 mol% of bridged ring compounds, 70 to 95 mol% of monovinyl aromatic compounds, and 0.5 to 10 mol% of divinyl aromatic compounds based on 100 mol% of the mixture. The definitions and examples of the bridged ring compounds, monovinyl aromatic compounds, and divinyl aromatic compounds are as described above, so they are not repeated here.
[0062] In some embodiments, step S103 may include polymerizing the mixture provided in step S101 at a polymerization temperature of 0 to 80° C. In some embodiments, the polymerization temperature may be 0 to 45° C., 0 to 40° C., 0 to 35° C., or 0 to 30° C. In some embodiments, step S103 may include polymerizing the mixture provided in step S101 using a catalyst. In some embodiments, the catalyst may include a boron trifluoride-ether complex (BF 3 -OEt 2 ), titanium tetrachloride (TiCl 4 ), or a combination thereof, but the present invention is not limited thereto.
[0063] In step S105, the crude composition obtained in step S103 is purified. In some embodiments, step S105 may include extracting the crude composition obtained in step S103 with isopropyl alcohol (IPA), but the present invention is not limited thereto. In some embodiments, step S105 may include extracting the crude composition obtained in step S103 with water. Step S107 of adding divinyl aromatic compound may be performed after step S105 as appropriate. Specifically, if the content of divinyl aromatic compound in the crude composition after purification in step S105 is less than 0.01 parts by weight based on 100 parts by weight of hydrocarbon resin polymer, or if the content of divinyl aromatic compound in the crude composition is to be adjusted, step S107 needs to be further performed, otherwise step S107 may be omitted. For example, in some embodiments, in embodiments where step S105 includes extracting the crude composition with water, step S107 may be omitted. In some embodiments, in embodiments where step S105 includes extracting the crude composition with isopropyl alcohol, step S107 may be performed after step S105, but the present invention is not limited thereto. The resin composition of the present invention can be obtained after step S105 or step S107.
[0064] The resin composition obtained by the method for preparing the resin composition of the present invention is as described above, so it is not described here in detail. The method for preparing the resin composition of the present invention can obtain a resin composition having at least one of the advantages of appropriate composition viscosity, low gel flow, low crosslinking temperature, short crosslinking time, high glass transition temperature, good electrical performance, and no smoke during the crosslinking process in a low-cost, low-energy, and / or environmentally friendly manner.
[0065] In some embodiments, the present invention provides a substrate structure. Figure 2 Schematic diagram of a substrate structure according to an embodiment of the present invention. Figure 2 As shown, the substrate structure of the present invention includes a base layer 200, a conductive layer 203 disposed on the base layer 200, and a resin layer 201 disposed between the conductive layer 203 and the base layer 200, wherein the resin layer 201 is formed by the above-mentioned resin composition through a cross-linking process.
[0066] In some embodiments, the base layer 200 may include polyimide (PI), polycarbonate (PC), polyethylene terephthalate (PET), glass, quartz, sapphire, ceramic, plastic, Ajinomoto Build-up Film (ABF), fiberglass paper, tissue paper, or any combination thereof, but the present invention is not limited thereto.
[0067] In some embodiments, the conductive layer 203 may include copper (Cu), aluminum (Al), molybdenum (Mo), tungsten (W), gold (Au), chromium (Cr), nickel (Ni), platinum (Pt), titanium (Ti), other suitable metal materials, or any combination thereof, but the present invention is not limited thereto. In some embodiments, the conductive layer 203 may have a single-layer structure or a multi-layer stacked structure. For example, the conductive layer 203 may include a single-layer metal copper.
[0068] The base layer 200 may have a first surface 200S1 and a second surface 200S2 opposite to the first surface 200S1 . The conductive layer 203 may be disposed on the first surface 200S1 of the base layer 200 , and the resin layer 201 may be disposed between the first surface 200S1 of the base layer 200 and the conductive layer 203 .
[0069] In some embodiments, the substrate structure may further include another conductive layer 204 on the second surface 200S2 of the base layer 200, and another resin layer 202 may be disposed between the second surface 200S2 of the base layer 200 and the conductive layer 204. Another resin layer 202 may include the same material as the resin layer 201. Another conductive layer 204 may include copper (Cu), aluminum (Al), molybdenum (Mo), tungsten (W), gold (Au), chromium (Cr), nickel (Ni), platinum (Pt), titanium (Ti), other suitable metal materials, or any combination of the foregoing, but the present invention is not limited thereto. In some embodiments, another conductive layer 204 may have a single-layer structure or a multi-layer stacked structure. Another conductive layer 204 may include the same or different materials and the same or different structures as the conductive layer 203. For example, another conductive layer 204 may include a single layer of metal copper.
[0070] The substrate structure having the above structure can be obtained in a low-cost, low-energy, and / or environmentally friendly manner. In addition, the substrate structure having the above structure can have at least one of good thermal performance (high glass transition temperature (Tg)) and electrical performance.
[0071] One or more embodiments of the present invention will now be described in detail with reference to the following examples. However, these examples are only used to illustrate the embodiments of the present invention and are not intended to limit the scope of the embodiments of the present invention.
[0072] [Preparation of polymers 1 to 15]
[0073] Polymer 1
[0074] Reaction Procedure
[0075] 203.1 g (20 mol%) of dicyclopentadiene (DCPD), 536 g (67 mol%) of styrene, 130 g (13 mol%) of divinylbenzene (DVB, purity 63%, the remaining 37% is ethylstyrene), and 1113.6 g of toluene were added to a 3 L four-necked straight jacket reactor under nitrogen, and stirred with a double-layer four-blade flat paddle set at a stirring speed of 400 rpm to form a mixture. 21.8 g of boron trifluoride diethyl ether complex (BF 3 -OEt 2 ) catalyst. After adding the catalyst, the reaction temperature was raised to 10°C and maintained for 10 minutes, then raised to 15°C and maintained for 3 hours. 65.4 g of isopropanol was added to terminate the polymerization reaction to obtain a polymer mother liquor, and it was confirmed that the viscosity of the polymer mother liquor at the time of termination was 4.7 cp.
[0076] Purification procedures
[0077] First, the polymer mother liquor was filtered to remove impurities and insolubles. The polymer mother liquor was stirred using a mechanical stirrer at a speed of 500 rpm. The polymer mother liquor was slowly dripped into 5 times the weight of isopropanol through a dropping funnel to obtain a white resin crude product. The solid-liquid phase was filtered by suction to obtain a white solid, and then the precipitation step of redissolving it in toluene (the weight ratio of mother liquor / isopropanol was 1:5) was repeated to obtain a purer white resin solid after filtration. The obtained white resin solid was washed with methanol to remove impurities and isopropanol, and finally heated and stirred under vacuum to remove the solvent to obtain a white powder hydrocarbon resin polymer as polymer 1.
[0078] Polymer 2
[0079] Reaction Procedure
[0080] 0.6498Kg (20mol%) of dicyclopentadiene (DCPD), 1.715Kg (67mol%) of styrene, 0.416Kg (13mol%) of divinylbenzene (purity 63%, the remaining 37% is ethylstyrene), and 3.5635Kg of toluene were added to a 10L four-neck straight jacket reactor under nitrogen, and stirred with a three-layer six-blade flat paddle with a stirring speed set to 200rpm to form a mixture. 0.06976Kg of boron trifluoride diethyl ether complex catalyst was injected at a rate of 0.25mL / min using a syringe pump at low temperature (0°C). After adding the catalyst, the reaction temperature was raised to 15°C, maintained for 10 minutes, and then raised to 20°C and maintained for 2 hours. After confirming that the viscosity of the polymer mother liquor was 11.67cp, 0.2092Kg of isopropanol was added to terminate the polymerization reaction.
[0081] Purification procedures
[0082] The impurities and insolubles in the polymer mother liquor were filtered out using a bag filter. Isopropanol (five times the weight of the polymer mother liquor) was injected into another large mixing tank equipped with a mechanical stirrer at a speed of 300 rpm using a pneumatic pump. The polymer mother liquor was then slowly injected using a hose pump (the speed was set at 100 rpm) to precipitate a white crude resin product in the tank. The solid-liquid phase was filtered through a large filter press to obtain a white solid, which was then repeated to obtain a purer white resin solid after re-dissolving it in toluene (the weight ratio of polymer mother liquor / isopropanol was 1:5) and filtering. The obtained white resin solid was washed with methanol to remove impurities and isopropanol, and finally heated and stirred under vacuum to remove the solvent to obtain a white powder hydrocarbon resin polymer as polymer 2.
[0083] Polymer 3
[0084] Reaction Procedure
[0085] 21.6 g (17 mol%) of dicyclopentadiene (95% purity), 70 g (70 mol%) of styrene (99.8% purity), 16.25 g (13 mol%) of divinylbenzene (63% purity, the remaining 37% is ethylstyrene) and 160 mL of toluene were added to a 1 L four-neck straight jacket reactor under nitrogen, and stirred with a single-layer four-blade flat paddle with a stirring speed set to 400 rpm to form a mixture. 2.73 g of boron trifluoride diethyl ether complex catalyst was injected at a rate of 0.25 mL / min using a syringe pump at low temperature (10°C). After adding the catalyst, the reaction was allowed to proceed for two hours. 8.1 g of isopropanol was added to terminate the polymerization reaction to obtain a polymer mother liquor.
[0086] Purification procedures
[0087] First, the polymer mother liquor was filtered to remove impurities and insolubles. The polymer mother liquor was stirred using a mechanical stirrer at a speed of 500 rpm. The polymer mother liquor was slowly dripped into 5 times the weight of isopropanol through a dropping funnel to obtain a white resin crude product. The solid-liquid phase was filtered by suction to obtain a white solid, and then the precipitation step of redissolving it in toluene (the weight ratio of polymer mother liquor / isopropanol was 1:5) was repeated to obtain a purer white resin solid after filtration. The obtained white resin solid was washed with methanol to remove impurities and isopropanol, and finally heated and stirred under vacuum to remove the solvent to obtain a white powder hydrocarbon resin polymer as polymer 3.
[0088] Polymer 4
[0089] Reaction Procedure
[0090] 69.70 g (87 mol%) of styrene, 13.02 g (13 mol%) of divinylbenzene (purity 63%, the remaining 37% is ethylstyrene), and 222.31 g of toluene were added to a 1 L four-neck straight jacket reactor under nitrogen, and stirred with a four-blade flat paddle with a stirring speed set at 400 rpm to form a mixture. 1.1 g of boron trifluoride diethyl ether complex catalyst was injected at a rate of 0.25 mL / min using a syringe pump at the reaction temperature (20° C.). After one and a half hours, 69 g of water was added to terminate the polymerization reaction to obtain a polymer mother liquor.
[0091] Purification procedures
[0092] First, the polymer mother liquor was filtered to remove impurities and insolubles. The polymer mother liquor was stirred using a mechanical stirrer at a rotation speed of 500 rpm. The polymer mother liquor was slowly dropped into 5 times the weight of isopropanol through a dropping funnel to obtain a white resin crude product. The solid-liquid phase was filtered by suction to obtain a white solid. The obtained white solid was washed with methanol to remove impurities and isopropanol, and finally heated at 60°C under nitrogen to remove the solvent, to obtain a white powder hydrocarbon resin polymer as polymer 4. The yield was about 50%.
[0093] Polymer 5
[0094] Reaction Procedure
[0095] 34.88 g (87 mol%) of styrene, 6.51 g (13 mol%) of divinylbenzene (purity 63%, the remaining 37% is ethylstyrene) and 222.63 g of toluene were added to a 1 L four-neck straight jacket reactor under nitrogen, and stirred with a four-blade flat paddle with a stirring speed set at 400 rpm to form a mixture. 1.1 g of boron trifluoride diethyl ether complex catalyst was injected at a speed of 0.25 mL / min using a syringe pump at the reaction temperature (20° C.). After four hours, 3.96 g of isopropanol was added to terminate the polymerization reaction to obtain a polymer mother liquor.
[0096] Purification procedures
[0097] First, the polymer mother liquor was diluted with 94 g of toluene. The polymer mother liquor was stirred using a mechanical stirrer at a rotation speed of 500 rpm. The polymer mother liquor was slowly dropped into 5 times the weight of isopropanol through a dropping funnel to obtain a white resin crude product. The solid-liquid phase was filtered by suction to obtain a white solid. The obtained white solid was washed with methanol to remove impurities and isopropanol, and finally heated at 60° C. under nitrogen to remove the solvent, to obtain a white powder hydrocarbon resin polymer as polymer 5. The yield was about 50%.
[0098] Polymer 6
[0099] Reaction Procedure
[0100] 3.59 g (5.7 mol%) of divinylbenzene (purity 63%, the remaining 37% is ethylstyrene) and 19.2 g (87 mol%) of styrene were added to a 250 mL round bottom flask under nitrogen. Then 20 g of xylene mixture was added to the above mixture at 25°C. 0.1 ml of 1 M TiCl 4 solution and 0.006 g of NaBArF 4 The polymerization reaction was initiated. After 30 minutes, the color of the mixture changed from colorless to red. 1 ml of isopropanol was added to terminate the polymerization reaction to obtain a polymer solution.
[0101] Purification procedures
[0102] The polymer solution was precipitated from isopropyl alcohol (IPA, 500 mL) to obtain an orange powder. The obtained orange powder was dried at 60° C. for 3 hours (yield = 18.6 g, 81%) to obtain polymer 6.
[0103] Polymer 7
[0104] Reaction Procedure
[0105] 21.58g (17mol%) of dicyclopentadiene (purity 95%), 52.99g (53mol%) of styrene (purity 99.8%), 37.50g (30mol%) of divinylbenzene (purity 63%, the remaining 37% is ethylstyrene) and 160mL of toluene are added to a 1L four-neck straight jacket reactor under nitrogen, and stirred with a single-layer four-blade flat paddle with a stirring speed set to 400rpm to form a mixture. 1.36g of boron trifluoride diethyl ether complex catalyst is injected at a speed of 0.25mL / min using a syringe pump at low temperature (0°C). After adding the catalyst, react for two hours, and add 4.1g of isopropanol to terminate the reaction to obtain a colorless polymer mother liquor.
[0106] Purification procedures
[0107] First, the polymer mother liquor was filtered to remove impurities and insolubles. The polymer mother liquor was stirred using a mechanical stirrer at a speed of 500 rpm. The polymer mother liquor was slowly dripped into 5 times the weight of isopropanol through a dropping funnel to obtain a white resin crude product. The solid-liquid phase was filtered by suction to obtain a white solid, and then the precipitation step of redissolving it in toluene (the weight ratio of polymer mother liquor / isopropanol was 1:5) was repeated to obtain a purer white resin solid after filtration. Finally, the solvent was removed by heating and stirring under vacuum to obtain 30.5 g of a white powder hydrocarbon resin polymer as polymer 7.
[0108] Polymer 8
[0109] Reaction Procedure
[0110] 21.58g (17mol%) of dicyclopentadiene (purity 95%), 56.99g (57mol%) of styrene (purity 99.8%), 32.50g (26mol%) of divinylbenzene (purity 63%, the remaining 37% is ethylstyrene) and 160mL of toluene are added to a 1L four-neck straight jacket reactor under nitrogen, and stirred with a single-layer four-blade flat paddle with a stirring speed set to 400rpm to form a mixture. 1.36g of boron trifluoride diethyl ether complex catalyst is injected at a speed of 0.25mL / min using a syringe pump at low temperature (0°C). After adding the catalyst, react for two hours, and add 4.1g of isopropanol to terminate the reaction to obtain a colorless polymer mother liquor.
[0111] Purification procedures
[0112] First, the polymer mother liquor was filtered to remove impurities and insolubles. The polymer mother liquor was stirred using a mechanical stirrer at a speed of 500 rpm. The polymer mother liquor was slowly dripped into 5 times the weight of isopropanol through a dropping funnel to obtain a white resin crude product. The solid-liquid phase was filtered by suction to obtain a white solid, and then the precipitation step of redissolving it in toluene (the weight ratio of polymer mother liquor / isopropanol was 1:5) was repeated to obtain a purer white resin solid after filtration. The obtained white resin solid was washed with methanol to remove impurities and isopropanol, and finally heated and stirred under vacuum to remove the solvent to obtain 35.7 g of a white powder hydrocarbon resin polymer as polymer 8.
[0113] Polymer 9
[0114] Reaction Procedure
[0115] 21.6g (17mol%) of dicyclopentadiene (purity 95%), 59.99g (60mol%) of styrene (purity 99.8%), 28.75g (23mol%) of divinylbenzene (purity 63%, the remaining 37% is ethylstyrene) and 160mL of toluene are added to a 1L four-necked straight jacket reactor under nitrogen, and stirred with a single-layer four-blade flat paddle with a stirring speed set to 400rpm to form a mixture. 2.73g of boron trifluoride diethyl ether complex catalyst is injected at a speed of 0.25mL / min using a syringe pump at low temperature (0°C). After adding the catalyst, react for two hours, and add 8.1g of isopropanol to terminate the polymerization reaction to obtain a colorless polymer mother liquor.
[0116] Purification procedures
[0117] First, the polymer mother liquor was filtered to remove impurities and insolubles. The polymer mother liquor was stirred using a mechanical stirrer at a speed of 500 rpm. The polymer mother liquor was slowly dripped into 5 times the weight of isopropanol through a dropping funnel to obtain a crude white resin product. The solid-liquid phase was filtered by suction to obtain a white solid, and then the precipitation step of redissolving it in toluene (the weight ratio of polymer mother liquor / isopropanol was 1:5) was repeated to obtain a purer white resin solid after filtration. The obtained white resin solid was washed with methanol to remove impurities and isopropanol, and finally heated and stirred under vacuum to remove the solvent to obtain 40.1 g of a white powder hydrocarbon resin polymer as polymer 9.
[0118] Polymer 10
[0119] Reaction Procedure
[0120] 24.9 g (30 mol%) of divinylbenzene (purity 63%, the remaining 37% is ethylstyrene) and 46.5 g of styrene (70 mol%) were added to a 250 mL round bottom flask under nitrogen. 60 g of toluene was added to the above mixture at 40 °C. 2.6 g of 1 M TiCl 4 The solution started polymerization. After 3 hours, the color of the mixture changed from colorless to red / brown. 1 ml of isopropanol was added to terminate the polymerization to obtain a polymer solution.
[0121] Purification procedures
[0122] The red polymer solution was precipitated from isopropyl alcohol (IPA, 500 mL) to obtain an orange powder. The resulting orange powder was dried at 60° C. for 3 hours (yield = 37.8 g, 53%) to obtain polymer 10.
[0123] Polymer 11
[0124] Reaction Procedure
[0125] 12.7 g (40 mol%) of divinylbenzene (purity 63%, the remaining 37% is ethylstyrene) and 15.3 g (60 mol%) of styrene were added to a 250 mL round bottom flask under nitrogen. 50 g of toluene was added to the above mixture at 75°C. 0.15 g of BF 3 .OET 2 The solution started polymerization. After 1.5 hours, the color of the mixture changed from colorless to yellow. 1 ml of isopropanol was added to terminate the polymerization to obtain a polymer solution.
[0126] Purification procedures
[0127] The red polymer solution was precipitated from isopropyl alcohol (IPA, 500 mL) to obtain an orange powder. The resulting orange powder was dried at 60° C. for 3 hours (yield = 16.0 g, 57%) to obtain polymer 11.
[0128] Polymer 12
[0129] Reaction Procedure
[0130] 37.49g (60mol%) of styrene, 15.63g (20mol%) of divinylbenzene (purity 63%, the remaining 37% is ethylstyrene), 15.864g (20mol%) of dicyclopentadiene (DCPD) and 173.4g of toluene were added to a 1L four-neck straight jacket reactor under nitrogen, and stirred with a four-blade flat paddle with a stirring speed set to 400rpm to form a mixture. 1.7g of boron trifluoride diethyl ether complex catalyst was injected at a speed of 0.25mL / min using a syringe pump at the reaction temperature (20°C). After three hours, 5.37g of isopropanol was added to terminate the polymerization reaction to obtain a polymer mother liquor.
[0131] Purification procedures
[0132] First, the polymer mother liquor was diluted with 62 g of toluene. The polymer mother liquor was stirred using a mechanical stirrer at a rotation speed of 500 rpm. The polymer mother liquor was slowly dropped into 5 times the weight of isopropanol through a dropping funnel to obtain a white resin crude product. The solid-liquid phase was filtered by suction to obtain a white solid. The obtained white solid was washed with methanol to remove impurities and isopropanol, and finally heated at 60° C. under nitrogen to remove the solvent, to obtain a white powder hydrocarbon resin polymer as polymer 12. The yield was about 38%.
[0133] Varnish solution containing polymer 13
[0134] Reaction Procedure
[0135] At 20°C, 20 mol% of dicyclopentadiene (DCPD), 13 mol% of divinylbenzene (purity 63%, the remaining 37% is ethylstyrene), 67 mol% of styrene and toluene were added to a 1L jacket reactor under nitrogen. Boron trifluoride diethyl ether complex catalyst was added to initiate the polymerization reaction. The color of the mixture slowly changed from colorless to brown. The reaction was stirred at 20°C for 1 hour, and then water was added to terminate the polymerization reaction to obtain a polymer mother liquor.
[0136] Purification procedures
[0137] First, the polymer mother liquid is filtered to remove impurities and water. The polymer mother liquid is then allowed to stand at room temperature for 0 to 30 minutes, the yellow layer is collected, and then concentrated using a rotary evaporator to obtain a 50 wt% varnish solution containing a hydrocarbon resin polymer (polymer 13). Analysis shows that the varnish solution containing polymer 13, based on 100 parts by weight of polymer 13, also contains 4.77 parts by weight of divinylbenzene, 3.5 parts by weight of ethylstyrene, 16 parts by weight of styrene, and 8.5 parts by weight of toluene.
[0138] Varnish solution containing polymer 14
[0139] Reaction Procedure
[0140] At 20°C, 20 mol% of dicyclopentadiene (DCPD), 13 mol% of divinylbenzene (purity 63%, the remaining 37% is ethylstyrene), 67 mol% of styrene and toluene were added to a 1L jacket reactor under nitrogen. Boron trifluoride diethyl ether complex catalyst was added to initiate the polymerization reaction. The color of the mixture slowly changed from colorless to brown. The reaction was stirred at 20°C for 2 hours, and then water was added to terminate the polymerization reaction to obtain a polymer mother liquor.
[0141] Purification procedures
[0142] First, the polymer mother liquid is filtered to remove impurities and water. The polymer mother liquid is then allowed to stand at room temperature for 0 to 30 minutes, the yellow layer is collected, and then concentrated using a rotary evaporator to obtain a 50 wt% varnish solution containing a hydrocarbon resin polymer (polymer 14). Analysis shows that the varnish solution containing polymer 14, based on 100 parts by weight of polymer 14, also contains 1.9 parts by weight of divinylbenzene, 1.8 parts by weight of ethylstyrene, 12 parts by weight of styrene, and 28 parts by weight of toluene.
[0143] The materials and their proportions used to prepare polymers 1 to 12 and the varnish solution containing polymers 13 and 14 are listed in the following Table 1, and the polymerization time, polymerization temperature, catalyst, and yield are listed in the following Table 2.
[0144] Table 1
[0145]
[0146]
[0147] Table 2
[0148]
[0149]
[0150] The nuclear magnetic resonance device (NMR, JEOL, JNM-ECZ400S) was used to analyze the 13 C-NMR and 1H-NMR was used to analyze the structural composition of polymers 1 to 14, and it was found that polymers 1 to 14 included repeating units (A) derived from a bridged ring compound, repeating units (B) derived from a monovinyl aromatic compound, and repeating units (C) derived from a divinyl aromatic compound. Table 3 discloses the content of repeating units (A) derived from a bridged ring compound, the content of repeating units (B) derived from a monovinyl aromatic compound, the content of repeating units (C) derived from a divinyl aromatic compound, and the total content of repeating units (A) and repeating units (C) in polymers 1 to 14.
[0151] Table 3
[0152]
[0153]
[0154] Measurement of physical / chemical properties of polymers 1 to 14
[0155] [Measurement of hydrogen content on reactive double bonds]
[0156] Polymers 1 to 14 were dissolved in deuterated chloroform (CDCl 3 ). The hydrogen content on the reactive double bonds of polymers 1 to 14 was measured by NMR (JEOL, JNM-ECZ400S / L1). Specifically, the hydrogen content on the reactive double bonds of polymers 1 to 14 was calculated by dividing the sum of the integral values of hydrogen on the reactive double bonds by the sum of the integral values of all hydrogen.
[0157] [Measurement of number average molecular weight (Mn) and polymer dispersity index (PDI)]
[0158] The number average molecular weight (Mn) and polymer dispersibility index (PDI) of Polymers 1 to 14 were measured by gel permeation chromatography (GPC) (Waters APC, column: Waters Acquity XT 900) using polystyrene as a standard.
[0159] Specifically, 5 mL of tetrahydrofuran (THF) was added to 0.01 g of polymer 1 to polymer 14 respectively to prepare samples of polymer 1 to polymer 14. After filtering the samples of polymer 1 to polymer 14 with a 0.22 μm filter, the number average molecular weight (Mn) and polymer dispersibility index (PDI) of polymer 1 to polymer 14 were obtained by instrumental analysis.
[0160] [Measurement of cross-linkable repeating unit content (C1)]
[0161] The structures of polymers 1 to 14 were analyzed by NMR (JEOL, JNM-ECZ400S / L1) and GPC (waters), CDCl 3 As solvent, CDCl 3 The resonance line of was used as an internal standard to obtain the content of the cross-linkable repeating unit (C1) in polymers 1 to 14.
[0162] The number average molecular weight (Mn), polymer dispersibility index (PDI), hydrogen content on reactive double bonds, and crosslinkable repeating unit content (C1) of polymers 1 to 14 are listed in Table 4 below.
[0163] Table 4
[0164]
[0165]
[0166] 100 parts by weight of polymers 1 to 12 are mixed with DVB, EVB, styrene, and toluene according to the ratios listed in Table 5-1 below to form a varnish solution containing these polymers (corresponding to the resin composition of the present invention). Then, other components are additionally added to obtain the compositions of Examples 1 to 45. In addition, the contents of each component in the varnish solution containing polymer 13 and the varnish solution containing polymer 14 (corresponding to the resin composition of the present invention) are disclosed in Table 5-2, and other components are additionally added according to the ratios listed in Table 5-2 to obtain the compositions of Examples 46 and 47. The values of the contents of each component listed in Tables 5-1 and 5-2 below are all expressed in parts by weight. For example, in Table 5-1, Example 1 includes 100 parts by weight of polymer 1, 100 parts by weight of toluene, 15 parts by weight of a toughening agent, 0.3 parts by weight of a peroxide, and 30 parts by weight of a filler. The toughening agent in Tables 5-1 and 5-2 may be a butadiene copolymer, such as Ricon 100 or Ricon 257; and the resin may be a polyphenylene ether, such as SA9000. The filler may be SVC purchased from Admatch or SS-10 purchased from Tokuyama. The peroxide may be perbutyl P purchased from NOF Corporation. In the example including the filler, the filler is ground with zirconium to a state uniformly dispersed in the composition.
[0167] Table 5-1
[0168]
[0169]
[0170]
[0171] Table 5-2
[0172]
[0173] Property Measurements of Substrate Samples of the Compositions of Examples 1 to 23, 46, and 47
[0174] Glass fiber cloth (Asahi 2116, Dk / Df=3.3 / 0.0030 at 28 GHz) was immersed in the compositions of Examples 1-23, 46, and 47, respectively, and then baked at 160°C for 7 minutes to obtain prepregs of Examples 1-23, 46, and 47. Two prepregs and two copper foil layers (RTF, Hoz (18 μm), Rz: 3.5 μm) were stacked together so that the two prepregs were located between the two copper foil layers, and a silane adhesive (KBM503) was applied between the copper foil layers and the prepregs. At a temperature of 180-210°C, a pressure of 441 psi was applied for 3 hours to obtain substrate samples of Examples 1-23, 46, and 47.
[0175] [Measurement of glass transition temperature (Tg)]
[0176] The substrate samples of Examples 1 to 23, 46, and 47 were heated from 25°C to 270°C at a rate of 3°C / min. The glass transition temperatures (Tg) of the substrate samples of Examples 1 to 23, 46, and 47 were measured using dynamic mechanical analysis (DMA, TA / Q800). The test frequency was 1 Hz. The glass transition temperatures (Tg) of the substrate samples of Examples 1 to 23, 46, and 47 were obtained from the tan Delta peak in the DMA graph.
[0177] [Thermal decomposition temperature (decomposition Temperature, Td)]
[0178] The thermal decomposition temperature (Td) of the substrate samples of Examples 1 to 23, 46, and 47 was measured by thermogravimetric analysis (TGA, TA / Q500). The test temperature range was from room temperature to 900° C. The heating rate was 10° C. / min, without nitrogen flow protection.
[0179] [Measurement of Resin Flow]
[0180] After the substrate sample is formed, the edge of the resin layer of the substrate sample is measured using a length measuring tool (e.g., a ruler) to determine the glue flow length. Specifically, the substrate sample includes a copper foil layer and a resin layer including the composition of Examples 1 to 23, 46, and 47, wherein the composition of Examples 1 to 23, 46, and 47 will partially overflow (i.e., exceed the glass fiber cloth) during the hot press curing stage, and the glue flow length is the average length of the composition of Examples 1 to 23, 46, and 47 that exceeds the edge of the glass fiber cloth.
[0181] [Measurement of Percent of Thermal Expansion (PTE)]
[0182] The analysis was performed using a thermomechanical analyzer (Thermomechanical Analysis, model: Q400, brand: TA) according to the following steps.
[0183] Execute Cycle 1 to Cycle 4 in sequence, and use Cycle 3 as the measurement reference to obtain the dimensions at different temperatures (50 and 260°C) to calculate the percentage of dimensional change. Cycle 1: Under N2 environment, balance at 25°C, keep constant temperature for 1 minute, and increase the temperature from 25°C to 270°C at 20°C / min. Cycle 2: Cool down from 270°C to 25°C at 20°C / min, keep constant temperature for 1 minute, and balance at 25°C. Cycle 3: Increase the temperature from 25°C to 270°C at 10°C / min. Cycle 4: Cool down from 270°C to 25°C at 20°C / min.
[0184] [Electrical performance test]
[0185] The Dk / Df of the substrate samples of Examples 1 to 23, 46, and 47 at 10 GHz, 28 GHz, and 40 GHz were measured using network analyzer software (network analyzer Keysight, P5007A, SCR).
[0186] [Peeling strength test]
[0187] Glass fiber cloth (Asahi 2116, 28 GHz Dk / Df=3.3 / 0.0030) was immersed in the compositions of Examples 1-23, 46, and 47, respectively, and then baked at 160°C for 7 minutes to obtain prepregs of Examples 1-23, 46, and 47. Silane adhesive (KBM503) was applied on the surface of the copper foil layer, and four prepregs were stacked with two copper foil layers (RTF, Hoz (18 μm), Rz: 3.5 μm) so that the four prepregs were located between the two copper foil layers, and silane adhesive (KBM503) was applied between the copper foil layer and the prepreg. At a temperature of 180-210°C, a pressure of 441 PSI was applied for 3 hours to obtain substrate samples of Examples 1-23, 46, and 47. Next, the peel strength of the substrate samples of Examples 1 to 23, 46, and 47 having a substrate sample size of 12.7 mm×20 mm was measured at a peel rate of 50.8 mm / min using SHIMADZU AG-Xplus.
[0188] The adhesive flow, peel strength, glass transition temperature, PTE, and Td of the substrate samples of Examples 1-23, 46, and 47 are listed in the following Table 6. The dielectric constant / loss factor (Dk / Df) of the substrate samples of Examples 1-23, 46, and 47 at 10 GHz, 28 GHz, and 40 GHz are listed in the following Table 7.
[0189] Table 6
[0190]
[0191]
[0192] Table 7
[0193]
[0194] ※The smoke phenomenon is observed by naked eyes (O: smoke. X: no smoke)
[0195] [Measurement of rheological properties]
[0196] 0.55 mL of the composition of Examples 24-45 was pipetted and placed on a rheometer (Rheometer, model: MCR302, brand: Anton Paar). A temperature sweep was performed with the following parameters to measure the changes in the rheological properties of the composition of Examples 24-45 in the temperature range of 40°C to 210°C: pre-equilibrium: shear rate = 1 (1 / s), for 60 seconds; hold time: 60 seconds (40°C); experimental temperature: 40-210°C; strain: 0.1%; frequency: 10 rad / s.
[0197] The measured rheological properties include loss modulus and storage modulus; the loss modulus is usually related to fluid properties. Therefore, it can be said that the loss modulus reflects the liquid behavior of the material; the storage modulus is usually related to solid properties. Therefore, it can be said that the storage modulus reflects the solid behavior of the material. When the temperature rises, the changes in the loss modulus and storage modulus can be used to understand the process of the resin composition changing from liquid to solid.
[0198] Figure 3 30 is a graph showing the relationship between the storage modulus and loss modulus of the composition of Example 30 and temperature. Figure 3 It can be seen that in the low temperature range, the loss modulus may be higher, indicating that the composition of Example 30 exhibits more liquid properties at low temperatures. At 146.89°C, the storage modulus begins to exceed the loss modulus, indicating that the composition of Example 30 gradually transforms into a solid state, because the composition of Example 30 begins to crosslink or cure. In a higher temperature range, the storage modulus of the composition of Example 30 is significantly higher than the loss modulus, indicating that the material mainly behaves in a solid state. The temperature at which the storage modulus of each composition begins to exceed the loss modulus is defined herein as the crosslinkable temperature. That is, according to Figure 3 , the cross-linkable temperature of the composition of Example 30 is about 146.89°C.
[0199] [Measurement of storage modulus at 2000 seconds]
[0200] 0.55 mL of the composition of Examples 24-45 was pipetted and placed on a rheometer (Model: MCR302, Brand: Anton Paar). A time scan was performed with the following parameters: pre-equilibrium: shear rate = 1 (1 / s), for 60 seconds; experimental temperature: 160°C; strain: 0.1%; frequency: 10 rad / s. The storage modulus of the composition of Examples 24-45 at 2,000 seconds was measured.
[0201] Figure 4 30 is a graph showing the relationship between the storage modulus and the loss modulus of the composition of Example 30 and time. Figure 4 It can be seen that at a cross-linking temperature of 160° C., the storage modulus of the composition of Example 30 increases with the increase of the cross-linking time, and the increase of the storage modulus tends to be flat until after a cross-linking time of 2,000 seconds. Figure 4 It can be seen that the storage modulus of the composition of Example 30 is 529,520 Pa after a crosslinking time of 2,000 seconds at a crosslinking temperature of 160°C.
[0202] [Measurement of required cross-linking time]
[0203] As above, in the time scan, the crosslinking time corresponding to the storage modulus obtained by multiplying the storage modulus of the composition of Examples 24 to 45 after 2,000 seconds of crosslinking time by 0.9 is defined as the "required crosslinking time". Figure 4 It can be seen that the storage modulus of the composition of Example 30 is 529,520 Pa after 2,000 seconds of crosslinking time at a crosslinking temperature of 160° C.; and its “required crosslinking time” is 1,490 seconds (i.e., the crosslinking time corresponding to reaching 476,568 Pa (0.9×529,520)).
[0204] [Measurement of composite viscosity of the composition at 1 / 2 of the required crosslinking time]
[0205] As above, during the time scan, the composite viscosity of the compositions of Examples 24 to 45 after half of the "required crosslinking time" was measured and recorded as "complex viscosity at 1 / 2 the required crosslinking time". Figure 5 is a graph showing the relationship between the composite viscosity and time of the composition of Example 30. Figure 5 It can be seen that after half of the "required cross-linking time" (i.e., 1,490 seconds / 2=745 seconds) at a cross-linking temperature of 160° C., the composite viscosity of the composition of Example 30 is 3.82×10 7 cP.
[0206] The measured cross-linkable temperature, required cross-linking time, composite viscosity at 1 / 2 the required cross-linking time, and storage modulus at 2000 seconds of the compositions of Examples 24 to 45 are listed in Table 8 below.
[0207] Table 8
[0208]
[0209]
[0210] Figure 6 3 is a graph showing the relationship between the glass transition temperature of the resin composition according to the present invention and the DVB content in the resin composition. Figure 6 (a) is a graph showing the relationship between the glass transition temperature of the substrate samples of Examples 1-4 and the DVB content in the compositions of Examples 1-4. Figure 6 (b) is a graph showing the relationship between the glass transition temperature of the substrate samples of Examples 5 to 11 and the DVB content in the compositions of Examples 5 to 11. Figure 6 (c) is a graph showing the relationship between the glass transition temperature of the substrate samples of Examples 12 to 15 and the DVB content in the compositions of Examples 12 to 15. Figure 6 It can be seen that the more DVB content in the resin composition, the higher the glass transition temperature. Figure 6(a) It can be seen that compared with the substrate sample of Example 1 (without DVB), the substrate samples of Examples 2 to 4 have higher glass transition temperatures. Figure 6 (b) It can be seen that compared with the substrate sample of Example 5 (without DVB), the substrate samples of Examples 7 to 11 have higher glass transition temperatures, and the glass transition temperature is proportional to the DVB content in the composition. Figure 6 (c) It can be seen that compared with the substrate sample of Example 12 (without DVB), the substrate samples of Examples 13 to 15 have higher glass transition temperatures, and the glass transition temperature is proportional to the DVB content in the composition.
[0211] Figure 7 4 is a graph showing the relationship between the flow of the resin composition according to the present invention and the content of DVB in the resin composition. Figure 7 (a) is a graph showing the relationship between the glue flow of the substrate samples of Examples 1 to 4 and the DVB content in the compositions of Examples 1 to 4. Figure 7 (b) is a graph showing the relationship between the flow of the substrate samples of Examples 5 to 11 and the DVB content in the compositions of Examples 5 to 11. Figure 7 (c) is a graph showing the relationship between the glue flow of the substrate samples of Examples 12 to 15 and the DVB content in the compositions of Examples 12 to 15. Figure 7 (a) It can be seen that compared with the substrate sample of Example 1 (without DVB), the glue flow phenomenon of the substrate samples of Examples 2 to 4 is improved, and the glue flow length is inversely proportional to the DVB content in the composition. Figure 7 (b) It can be seen that compared with the substrate sample of Example 5 (without DVB), the glue flow phenomenon of the substrate samples of Examples 7 to 11 is improved, and the glue flow length is inversely proportional to the DVB content in the composition. Figure 7 (c) It can be seen that, compared with the substrate sample of Example 12 (without DVB), the glue flow phenomenon of the substrate sample of Example 15 is improved.
[0212] It can be seen from Table 7 that the composition of the present invention has excellent electrical performance. Specifically, compared with the substrate samples of Examples 16 to 18 (containing TAIC but not containing DVB), the loss factors (Df) of the substrate samples of Examples 13 to 15 (containing DVB but not containing TAIC) at 10 GHz, 28 GHz, and 40 GHz are all reduced (i.e., all improved). Figure 8 13 to 18 are graphs showing the relationship between the loss factor (Df) of the substrate samples and the DVB / TAIC content in the resin composition. Figure 8 It can be seen that DVB has better electrical performance (lower Df) than TAIC with the same content. Figure 8It can be seen that when the composition of the present invention is subsequently used to make prepreg and copper foil substrate, it is not necessary to use the conventional triallyl isocyanurate (TAIC) crosslinking agent to complete the substrate sample with excellent electrical properties.
[0213] In addition, since the composition of the present invention does not need to add TAIC crosslinking agent when making prepreg and copper foil substrate, smoke will not occur naturally. On the other hand, compared with TAIC crosslinking agent, the presence of DVB in the composition can also improve the solubility of hydrocarbon resin polymer, thereby having better processability.
[0214] According to Table 8, when the same polymer is included, Examples 28, 30, 32, 34, and 40 including 0.01 parts by weight or more of DVB have lower "crosslinkable temperatures" and / or lower "required crosslinking times" compared to Examples 29, 31, 33, 35, and 41 not including DVB. Accordingly, it can be seen that when the same polymer is included, 0.01 to 50 parts by weight of DVB can be included to perform a crosslinking reaction in a shorter time and / or at a lower temperature, thereby reducing the energy consumption required for the crosslinking reaction.
[0215] 100 parts by weight of polymer 1 and 100 parts by weight of toluene were mixed to prepare composition A; 10 parts by weight of DVB, 100 parts by weight of polymer 1 and 100 parts by weight of toluene were mixed to prepare composition B; 20 parts by weight of DVB, 100 parts by weight of polymer 1 and 100 parts by weight of toluene were mixed to prepare composition C. The viscosities of compositions A to C at 25 degrees Celsius were measured using a TOKI SANGYO electromagnetic force equilibrium viscometer. The measured viscosity results are listed in the following Table 9. The numerical values of the content of each component in the following Table 9 are all expressed in parts by weight.
[0216] Table 9
[0217] Composition A Composition B Composition C DVB (parts by weight) 0 10 20 Polymer 1 (parts by weight) 100 100 100 Toluene (parts by weight) 100 100 100 Viscosity (cp) 271.1 203.8 143.9
[0218] As can be seen from Table 9, the presence of DVB in the composition can reduce the viscosity of the resin composition, thereby having better processability. Specifically, compared with composition A without DVB, the viscosity of composition B and composition C containing DVB is significantly reduced.
[0219] According to the various embodiments and test results described above, it can be seen that when preparing the resin composition of the present invention, some embodiments do not require the use of organic solvents for purification, which is more environmentally friendly and can reduce costs. Since the resin composition of the present invention has low composition viscosity, low cross-linking temperature, and short required cross-linking time, the use of the resin composition of the present invention to manufacture a substrate structure can have the advantages of low energy consumption, low cost, and / or environmental friendliness. In addition, the use of the resin composition of the present invention to manufacture a substrate structure will not produce smoke and improve the glue flow phenomenon. The substrate structure manufactured using the resin composition of the present invention also has good thermal properties (high glass transition temperature (glass transition temperature, Tg)) and / or electrical performance advantages.
[0220] The features of the above embodiments are helpful for those with ordinary knowledge in the art to understand the present invention. Those with ordinary knowledge in the art should understand that the present invention can be used as a basis to design and change other processes and structures to achieve the same purpose and / or the same advantages of the above embodiments. Those with ordinary knowledge in the art should also understand that these equivalent substitutions do not depart from the spirit and scope of the present invention, and can be changed, replaced, or modified without departing from the spirit and scope of the present invention.
Claims
1. A resin composition comprising: 100 parts by weight of hydrocarbon resin polymer; as well as 0.01 to 50 parts by weight of a divinyl aromatic compound. 2 . The resin composition according to claim 1 , further comprising 5 to 350 parts by weight of a solvent.
3. The resin composition as claimed in claim 1, wherein based on 100 mol % of the hydrocarbon resin polymer, the hydrocarbon resin polymer comprises: 15 to 95 mol% of repeating units (B) derived from monovinyl aromatic compounds; as well as 5 to 85 mol% of repeating units (C) are derived from divinyl aromatic compounds.
4. The resin composition as claimed in claim 3, wherein the hydrocarbon resin polymer comprises 0.15-15 mol% of the repeating unit (A) derived from the bridged ring compound, based on 100 mol% of the hydrocarbon resin polymer.
5. The resin composition as claimed in claim 4, wherein based on 100 mol % of the hydrocarbon resin polymer, the sum of the contents of the repeating unit (A) and the repeating unit (C) of the hydrocarbon resin polymer is greater than or equal to 13 mol %.
6. The resin composition as claimed in claim 3 or 4, wherein the hydrogen content on the reactive double bonds of the hydrocarbon resin polymer is less than 10%.
7. The resin composition as claimed in claim 3 or 4, wherein the number average molecular weight (Mn) of the hydrocarbon resin polymer is 2,500 to 15,000 g / mol.
8. The resin composition of claim 3 or 4, wherein the molecular weight distribution index (PDI) of the hydrocarbon resin polymer is less than 20.
9. The resin composition as claimed in claim 3, wherein the repeating unit (C) comprises a crosslinkable repeating unit (C1) and a crosslinked repeating unit (C2): wherein R1, R2, R3, and R4 are each independently H or C 1-20 Alkyl, and Ar1 and Ar2 are phenylene groups; * represents the connection position between the cross-linkable repeating unit (C1) and / or the cross-linked repeating unit (C2) and other groups or units; and The content of the cross-linkable repeating unit (C1) is 1 to 30 mol % based on 100 mol % of the hydrocarbon resin polymer.
10. The resin composition as claimed in claim 1, wherein the resin composition has a cross-linkable temperature of 125°C to 165°C. 11 . The resin composition as claimed in claim 1 , wherein the resin composition has a storage modulus of 10,000 to 10,000,000 Pa after being cross-linked at a cross-linking temperature of 160° C. and a cross-linking time of 2,000 seconds. 12 . The resin composition as claimed in claim 11 , wherein the crosslinking time required for the resin composition to reach 0.9 times of the storage modulus is 1300 to 1900 seconds.
13. The resin composition as claimed in claim 12, wherein the resin composition has a crosslinking temperature of 160°C after half of the required crosslinking time of 1.00×10 4 ~6.00×10 8 Composite viscosity of cP.
14. A method for producing a resin composition, comprising the following steps: Providing a mixture, wherein the mixture includes an optional bridged ring compound, a monovinyl aromatic compound, and a divinyl aromatic compound; polymerizing the mixture to form a crude composition; as well as purifying the crude composition to obtain a resin composition, The resin composition comprises: 100 parts by weight of hydrocarbon resin polymer; as well as 0.01 to 50 parts by weight of a divinyl aromatic compound. 15 . The method for producing a resin composition as claimed in claim 14 , wherein the step of purifying the crude composition comprises extracting the crude composition with water. 16 . The method for producing a resin composition as claimed in claim 14 , further comprising a step of adding a divinyl aromatic compound after the step of purifying the crude composition. 17 . The method for producing a resin composition as claimed in claim 16 , wherein the step of purifying the crude composition comprises extracting the crude composition with isopropyl alcohol (IPA).
18. The method for producing a resin composition as claimed in claim 14, wherein based on 100 mol % of the hydrocarbon resin polymer, the hydrocarbon resin polymer comprises: 15 to 95 mol% of repeating units (B) derived from the monovinyl aromatic compound; as well as 5 to 85 mol% of the repeating units (C) are derived from the divinyl aromatic compound.
19. The method for producing a resin composition as claimed in claim 18, wherein the hydrocarbon resin polymer comprises 0.15-15 mol% of a repeating unit (A) derived from the bridged ring compound, based on 100 mol% of the hydrocarbon resin polymer.
20. A substrate structure, comprising: a resin layer, and a conductive layer disposed on the resin layer; The resin layer is formed by a resin composition through a cross-linking process, and the resin composition includes: 100 parts by weight of hydrocarbon resin polymer; as well as 0.01 to 50 parts by weight of a divinyl aromatic compound. 21 . The substrate structure of claim 20 , wherein the cross-linking process does not use triallyl isocyanurate (TAIC) cross-linking agent.
22. The substrate structure of claim 20, wherein the cross-linking process comprises a cross-linking temperature of 125°C to 165°C.
23. The substrate structure of claim 20, wherein based on 100 mol % of the hydrocarbon resin polymer, the hydrocarbon resin polymer comprises: 15 to 95 mol% of repeating units (B) derived from monovinyl aromatic compounds; as well as 5 to 85 mol% of the repeating units (C) are derived from divinyl aromatic compounds. 24 . The substrate structure of claim 20 , wherein the hydrocarbon resin polymer comprises 0.15-15 mol % of a repeating unit (A) derived from a bridged ring compound, based on 100 mol % of the hydrocarbon resin polymer.